(untitled) (Kinesiology, 2023)
This study aimed to compare tactical behaviour and performance of football players with different on-theball skills execution functional technical asymmetry levels and to verify whether functional technical and tactical performance indexes of football players are associated. The sample included 59 football players (14.2 ± 1.5 years of age). FUT-SAT and SAFALL-FOOT were used as instruments for performance analysis. Participants were divided in two groups: higher and lower functional technical asymmetry. Student’s t-test was used to compare the behaviour and tactical performance of the groups, and the Pearson test was used to verify associations between functional technical asymmetry and tactical performance indexes. A significance level of 5% was adopted. The higher functional technical asymmetry group showed less tactical efficiency (t57 = 1.9; p = .05; d = .17) and low performance results in the execution of defensive actions (t57 = 2.1; p = .04; d = .55; t57 = 2.1; p = .04; d = .61) compared to the lower functional technical asymmetry group. No association was found between the functional technical asymmetry and tactical performance indexes (r = -.06; p = .66). It is concluded that the levels of functional technical asymmetry affected the behaviour and tactical performance of players although functional technical asymmetry and tactical performance indexes values are not associated. Future investigations may verify how football players with high and low levels of functional technical asymmetry change their behaviour and tactical performance from different kinds of training. Key words: decision-making, motor behaviour, motor skills, performance analysis, team sports